2nd International Conference for Innovation in Biomedical Engineering and Life Sciences : ICIBEL 2017 (in conjunction with APCMBE 2017), 10-13 December 2017, Penang, Malaysia /: ICIBEL 2017 (in conjunction with APCMBE 2017), 10-13 December 2017, Penang, Malaysia. (2018) - Unknown
No abstract available